(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Generics are drugs marketed by their chemical names, not brand names or chemical compositions. Generic drugs are less expensive. The United States Food and Drug Administration (USFDA) allows generic drugs when patents expire or owners renounce their rights. Competition lowers drug prices once generics are accessible. The Food and Drug Administration monitors the drug business. The Senate confirms the Food and Drug Administration Commissioner's nomination. Food and medications are controlled less than lasers, cell phones, and condoms. The Food & Drug Administration designated 1938–1962 medications as "pioneer goods. Kefauver-Harris requires all drug firms to submit accelerated applications (Abbreviated New Drug Application). Medicaid and Medicare modifications to the Social Security Act popularised generic medications. The 1984 law accelerated the launch of generic pharmaceuticals law and boosted generic drug introduction. The 1992 Generic Medication Enforcement Act combats fraud and misuse. The 1984 law accelerated the launch of generic pharmaceuticals.